Prognostic Pathways Guide Drug Indications in Pan-Cancers - Meng, Fanlin; Zhang, Kenan; Yang, Changlin; Zhang, Ke; Xu, Quan; Ren, Ruifang; Zhou, Yiming; Sun, Yimin; Peng, Yan; Li, Yanze; Guo, Hongyan; Ren, Yonghong; et al. (Frontiers in Oncology, 2022)
Pathway-level analysis is a powerful approach enabling interpretation of post-genomic data at a higher level than that of individual molecules. Molecular-targeted therapy focusing on the cascade signaling pathways become a new paradigm in anticancer therapy, instead of a single protein. However, the approaches to narrow down the long list of biological pathways is limited. Here, we proposed a strategy for in silico Drug Prescription on biological pathways across pan-Cancers (CDP), by connecting drugs to candidate pathways. Applying on a list of 120 Traditional Chinese Medicines (TCM), we specially identified “TCM-pathways-cancers” triplets and constructed into a heterogeneous network across pan-cancers. Application into TCMs, the computational prescribing methods deepened the understanding of the efficacy of TCM in molecular level. Further application into western medicines, CDP could promote drug reposition avoiding time-consuming developments of new drugs.